Mendesain Rintisan Organisasi Sosial: Studi Kasus pada Organisasi Community Youth Development Surabaya - Arifianto, Taufan (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2025)
DESIGNING NEWLY INITIATED SOCIAL ORGANIZATION: A CASE STUDY OF COMMUNITY YOUTH DEVELOPMENT IN SURABAYA. Organizations aiming for social change are potential subjects of da'wah that contribute through their programs. Prior to developing such programs, newly established social organizations need to design their organization that encompasses essential components such as vision, mission, core values, organizational form, and structure, so those reflect the founding value of the organization. Community Youth Development (CYD) is a social organization that engages and empowers the youth of RW 12 Putat Jaya in various community initiatives in Kampung Dolly. As a newly initiated organization, CYD need to design its organizational anatomy as a foundation for their programs. This study uses Participatory Action Research (PAR) method, involving CYD’s key stakeholders as active participants in exploring, analyzing and developing organizational design. The study showed: (1) there are eight essential components in designing a newly initiated social organization; (2) the design process follows a sequential structure with vision and mission as the determining elements; (3) the formulation of the vision and mission takes into account the founder’s essential capital; and (4) the organization’s core values are grounded in the founder’s principles, which are reflected in the distinctive manner in which the vision and mission are implemented. These findings are expected to serve as a practical guide in developing holistic, systematic, and value-driven designs for social da'wah organizations.